How Combined Macrolide Nanomaterials are Effective Against Resistant Pathogens? A Comprehensive Review of the Literature - Siraj EA; Yayehrad AT; Belete A (International Journal of Nanomedicine, 2023)
Ebrahim Abdela Siraj,1,2 Ashagrachew Tewabe Yayehrad,1 Anteneh Belete2 1Department of Pharmacy, School of Health Sciences, College of Medicine and Health Sciences, Bahir Dar University, Bahir Dar, Ethiopia; 2Department of Pharmaceutics and Social Pharmacy, School of Pharmacy, College of Medicine and Health Sciences, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Ebrahim Abdela Siraj, Department of Pharmacy, Bahir Dar University, PO Box: 79, Bahir Dar, Ethiopia, Tel +251 918020093, Email ibrahim.abdela2008@gmail.comAbstract: Macrolide drugs are among the broad-spectrum antibiotics that are considered as “miracle drugs” against infectious diseases that lead to higher morbidity and mortality rates. Nevertheless, their effectiveness is currently at risk owing to the presence of devastating, antimicrobial-resistant microbes. In view of this challenge, nanotechnology-driven innovations are currently being anticipated for promising approaches to overcome antimicrobial resistance. Nowadays, various nanostructures are being developed for the delivery of antimicrobials to counter drug-resistant microbial strains through different mechanisms. Metallic nanoparticle-based delivery of macrolides, particularly using silver and gold nanoparticles (AgNPs & AuNPs), demonstrated a promising outcome with worthy stability, oxidation resistance, and biocompatibility. Similarly, macrolide-conjugated magnetic NPs resulted in an augmented antimicrobial activity and reduced bacterial cell viability against resistant microbes. Liposomal delivery of macrolides also showed favorable synergistic antimicrobial activities in vitro against resistant strains. Loading macrolide drugs into various polymeric nanomaterials resulted in an enhanced zone of inhibition. Intercalated nanomaterials also conveyed an outstanding macrolide delivery characteristic with efficient targeting and controlled drug release against infectious microbes. This review abridges several nano-based delivery approaches for macrolide drugs along with their recent achievements, challenges, and future perspectives.Keywords: macrolides, nanomedicine, drug resistance, macrolide nano-delivery